2017
DOI: 10.1186/s13073-017-0479-0
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation mapping: a novel approach for detection of pathogenic structural variants with a potential utility in clinical diagnosis

Abstract: BackgroundMassively parallel DNA sequencing, such as exome sequencing, has become a routine clinical procedure to identify pathogenic variants responsible for a patient’s phenotype. Exome sequencing has the capability of reliably identifying inherited and de novo single-nucleotide variants, small insertions, and deletions. However, due to the use of 100–300-bp fragment reads, this platform is not well powered to sensitively identify moderate to large structural variants (SV), such as insertions, deletions, inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 11 publications
(14 reference statements)
0
90
0
Order By: Relevance
“…18,19 Finally, optical mapping and electronic mapping provide an orthogonal approach capable of determining the approximate size and location of insertions, deletions, inversions, and translocations while spanning even very large SVs. [20][21][22] GIAB recently published benchmark sets for small variants for seven genomes, 9,23 and the Global Alliance for Genomics and Health Benchmarking Team established best practices for using these and other benchmark sets to benchmark germline variants. 24 These benchmark sets are widely used in developing, optimizing, and demonstrating new technologies and bioinformatics methods, as well as part of clinical laboratory validation.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Finally, optical mapping and electronic mapping provide an orthogonal approach capable of determining the approximate size and location of insertions, deletions, inversions, and translocations while spanning even very large SVs. [20][21][22] GIAB recently published benchmark sets for small variants for seven genomes, 9,23 and the Global Alliance for Genomics and Health Benchmarking Team established best practices for using these and other benchmark sets to benchmark germline variants. 24 These benchmark sets are widely used in developing, optimizing, and demonstrating new technologies and bioinformatics methods, as well as part of clinical laboratory validation.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of structural variants is key for the diagnostics of genetic disorders. Recent work from Barseghyan et al 10 illustrates this by showing how genome imaging correctly diagnoses Duchenne Muscular Dystrophy from clinical samples. In a another study a prostate tumor sample was profiled by comparing the cancer sample with matched blood by genome imaging.…”
Section: Discussionmentioning
confidence: 98%
“…Label pattern differences relative to a reference are detected and these differences are used to call structural variants (SVs). 10 Because of the unique value gained by optical mapping of ultra-long DNA reads, it has been used in essentially all modern reference genome assemblies (human GRCh, 11; 12 mouse, 13 goat, 14 maize, 15 as well as benchmark structural variation papers. 16-18…”
Section: Introductionmentioning
confidence: 99%
“…The absence of Southern Blot analysis of fetal tissue is a limitation of the current study but some samples have demonstrated the application of Bionano optical mapping in the FSHD1 gene diagnosis. Besides, Bioano optical mapping can detect chromosome deletion, repeat, inversion . Qian Zhang et al used this method to detect a repetition of a 4q35 region successfully.…”
Section: Discussionmentioning
confidence: 99%